The Relationship Between Pregnant Women's Knowledge of Triple Elimination Screening and Their Satisfaction with the Service - Gusti Ayu Putu Ardianti Utami; Ni Luh Gede Puspita Yanti; Diah Prihatiningsih (CV. CENDIKIA JENIUS INDONESIA, 2026)
Triple Elimination screening is a strategic effort to prevent the transmission of HIV, syphilis, and hepatitis B from mother to infant; however, its coverage and quality of implementation at primary healthcare facilities remain suboptimal. This study aimed to analyze the relationship between pregnant women’s knowledge of Triple Elimination screening and their level of satisfaction with services at UPTD Puskesmas Banjar II. An analytic correlational study with a cross-sectional design was conducted. The sample consisted of 70 first-trimester pregnant women selected using accidental sampling. Data were collected using structured questionnaires measuring knowledge levels and service satisfaction and were analyzed using the Chi-square test. The results showed that most respondents had a good level of knowledge (40%) and reported satisfaction with the services (62.9%). Bivariate analysis revealed a significant relationship between pregnant women’s knowledge and satisfaction with Triple Elimination screening services (p = 0.000). These findings indicate that improving pregnant women’s knowledge plays an important role in shaping positive perceptions of service quality. Therefore, optimizing health education is recommended to enhance service satisfaction and the success of the Triple Elimination program.